Using virtual reality to enhances efforts for introduce cultural heritage - Arfin Sadiq, Zeinel (Universitas Ahmad Dahlan, 2022)
At present, cultural heritage is in a dangerous condition and it is all influenced by several factors such as natural disasters and man-made disasters. For example, in Indonesia in March 2018 there was a destruction of the Dayak Indigenous Sites whose cases were damaged due to human factors, not to mention talking about the destruction of damaged cultural sites such as in several countries such as Iraq, Syria, Afghanistan & Indonesia. The use of technology-based Virtual Reality (VR) in maintaining cultural heritage is very important because the identity that is in cultural heritage is the foundation of evidence of human life in the past. Threats in the form of human behavior and natural disasters have an impact of erasing historical and cultural traces which could threaten a nation in relation to the main national interests of a country. Maximizing the benefits of technological advancements by using Virtual Reality as an alternative to preserve cultural heritage & cultural exploration, this utilization can lower the cost of study of cultural exploration such as exploration of cultural heritage locations that are far especially in transport costs.